The Florida Bull Test, 2013–2014 - Vitor R. G. Mercadante; G. Cliff Lamb (EDIS)
The 2013-2014 Florida Bull Test was a 112-day performance test and a breeding soundness evaluation of each bull that qualified for the auction. Table 1 summarizes feed efficiency data; Table 2 individual feed intake and feed efficiency; and Table 3 individual animal performance. This 10-page fact sheet was written by Vitor R. G. Mercadante, G. Cliff Lamb, and Nicolas DiLorenzo, and published by the UF Department of Animal Sciences, May 2014.